Poly(alkylimidazolium bis(trifluoromethylsulfonyl)imide)‐Based Polymerized Ionic Liquids: A Potential High‐Performance Lubricating Grease. Issue 5 (16th January 2019) - Wu, Jian; Mu, Liwen; Feng, Xin; Lu, Xiaohua; Larsson, Roland; Shi, Yijun
Abstract: Polymers prepared from ionic liquids are widely called polymerized ionic liquids (PILs). Compared to monocationic and dicationic ILs, PILs have higher molecular weights, charge, and greater intermolecular interactions, which make PILs have a higher possibility to generate better lubricity. PILs of poly‐alkylimidazolium bis(trifluoromethylsulfonyl)imide (PImC6 NTf2 ) is studied herein. Dicationic ILs of 1, 1′‐(pentane‐1, 5‐diyl)‐bis(3‐butylimidazolium) bis(trifluoromethylsulfonyl)imide (BIm5 ‐(NTf2 )2 ) is used as additive to decrease the crystallization temperature of PImC6 NTf2 . Lubricity of PImC6 NTf2 and PImC6 NTf2 +BIm5 ‐(NTf2 )2, as well as BIm5 ‐(NTf2 )2 for comparison is evaluated under severe conditions, i.e., 3.0 to 3.5 GPa and 200 °C. The rheological study suggests that PImC6 NTf2 can be classified into grease. Tribological test results show that PImC6 NTf2 has much better antiwear property than BIm5 ‐(NTf2 )2, especially at 3.5 GPa. Adding 4% BIm5 ‐(NTf2 )2 to PImC6 NTf2 is able to reduce friction under high pressure. At 200 °C, PImC6 NTf2 exhibits excellent lubricity. The mixture of 96%PImC6 NTf2 +4%BIm5 ‐(NTf2 )2 shows even better antiwear property than neat PImC6 NTf2 and exhibits the highest friction reducing property among the ILs at 200 °C. It is speculated that the robust strength of PILs and strong adhesion between PILs and solids are key factors in achieving the excellent antiwear property. Abstract : Poly(alkylimidazolium bis(trifluoromethylsulfonyl)imide)‐based polymerized ionic liquids (PImC6 NTf2 ) are studied as a potential high‐performance lubricating grease. Diimidazolium ILs of 1, 1′‐(pentane‐1, 5‐diyl)‐bis(3‐butylimidazolium) bis(trifluoromethylsulfonyl)imide (BIm5 ‐(NTf2 )2 ) is used as additive to decrease the crystallization temperature of PImC6 NTf2 . PImC6 NTf2 has much better antiwear property than BIm5 ‐(NTf2 )2 under high pressure. 96%PImC6 NTf2 +4%BIm5 ‐(NTf2 )2 shows higher lubricity than PImC6 NTf2 and exhibits the lowest friction coefficient among the ILs at 200 °C.